Implementasi Upaya Pemerintah dalam Peningkatan Kesadaran Membayar Zakat Berdasarkan PSAK 109 pada Baznas Kota Pangkalpinang - Hendarti Tri Setyo Mulyani; Yuni Iswanto (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2023)
Abstract-This research is a qualitative descriptive research whichaims to analyze the application of zakah and infaq/shadaqahaccounting at the BAZNAS Pangkalpinang City.The method of data collection in this research is a field researchthrough interview, observastion, and literature view. The interviewwas conducted with a leader of BAZNAS Pangkalpinang City andalso with the financing and executor reporting department andadministration.The result of this research shows that if not all the points of PSAK109 have been applied by BAZNAS Pangkalpinang City. Theincompatibility are in the recognition of non-cash infaq/shadaqah, theseperation of amil fund when muzaki determines mustahik and thedisclousure of various accounting policies in the notes of financialstatement.